Legal Impact of the Division of Mandatory Government Affairs to the Society - Purwanda, Sunardi (Fakultas Hukum Universitas Lampung, 2024)
This article examines the division of concurrent authority between the central and local governments in Mandatory Government Affairs and its implications for fulfilling citizens’ basic service rights. Using an interdisciplinary legal approach, the research explores the persistence of centralized bureaucratic influence in regional governance and evaluates whether the current separation of mandatory affairs aligns with regional needs or hampers local welfare. Findings indicate that the central government continues to dominate decision-making due to the legacy of centralized bureaucracy. The authority division under Article 12 paragraphs (1) and (2) creates legal ambiguities, conflicts with principles of good governance, and undermines interrelated human rights. Consequently, these issues impact the formulation of Regional Revenue and Expenditure Budgets (APBD), impeding the welfare of communities, as exemplified by the case of Parepare City.